2006
DOI: 10.1177/0164027506292241
|View full text |Cite
|
Sign up to set email alerts
|

Productive Activity in Later Life

Abstract: The authors examined time spent on paid and unpaid work across the life course and historically to reflect on connections between activity patterns and macroeconomic events. The authors conducted quasi-cohort analysis on timeuse data over 30 years to examine trends in paid and unpaid work. Women aged 40 years and older spent more time on paid work and less time on unpaid work between 1971 and 1998. Men's paid work time decreased between 1971 and 1981 and between 1992 and 1998 but increased between 1981 and 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Participants consistently reported decreased participation in productive activities over the previous 5 years, as well as across the three decades of older adulthood, with the 65–74 year-old participants maintaining the highest level of participation. As supported by previous research, participants reported decreases in specific activities such as volunteer work, care for others, home repairs, and heavy housework (Johnson and Schaner, 2004; Fast et al, 2006; Krantz-Kent and Stewart, 2007). Previous literature suggests that domestic activities are maintained at a higher participation rate than other productive activities (Gauthier and Smeeding, 2003; Krantz-Kent, 2005), however, this was only true for light housework.…”
Section: Discussionsupporting
confidence: 63%
“…Participants consistently reported decreased participation in productive activities over the previous 5 years, as well as across the three decades of older adulthood, with the 65–74 year-old participants maintaining the highest level of participation. As supported by previous research, participants reported decreases in specific activities such as volunteer work, care for others, home repairs, and heavy housework (Johnson and Schaner, 2004; Fast et al, 2006; Krantz-Kent and Stewart, 2007). Previous literature suggests that domestic activities are maintained at a higher participation rate than other productive activities (Gauthier and Smeeding, 2003; Krantz-Kent, 2005), however, this was only true for light housework.…”
Section: Discussionsupporting
confidence: 63%
“…First, previous studies have documented heterogeneous interrelationships between pairs of activities which appear to depend on the type and intensity of the involvement. Second, a large portion of previous evidence focused on only informal care and volunteering as unpaid forms of work, rarely considering other activities that have been shown to influence overall allocation of time, such as leisure activities and housework (Dosman et al , 2006; Fast et al , 2006; Dury et al , 2016). Third, the few studies that have examined latent patterns of paid and unpaid work are cross-sectional.…”
Section: Paid and Unpaid Work: Complementary Or Competing Activities?mentioning
confidence: 99%
“…Many studies tend to focus on a single or limited number of activity domains, such as physical activity [14,17], informal and formal social activity [18,19], solitary or sedentary behavior [19] and leisure activity [17,18,20]. Other researchers have focused directly on productive activity engagement in later life, such as paid work, caregiving and volunteering [21][22][23][24][25][26]. While these studies contribute to the literature on activity and well-being outcomes in later life, they often ignore the reality that most people engage in multiple activities simultaneously on a daily basis, and a series of activities can compete with and complement each other.…”
Section: Introductionmentioning
confidence: 99%